1996
DOI: 10.1002/(sici)1099-0488(199605)34:7<1257::aid-polb7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation of PVC below the yield point

Abstract: Stress relaxation of commercial poly(vinyl chloride) (PVC) is measured at strains below 3% and at different temperatures below the glass transition temperature. First it is shown that below the yield point the material follows a linear viscoelastic behavior. Then the data at a fixed deformation level (0.03) are fitted by considering a lognormal distribution function of relaxation times. Furthermore, from the measured stress‐strain curves, the temperature dependence of the elastic tensile modulus is determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 3 publications
5
24
0
Order By: Relevance
“…Previous observations on this elastomer indicated that most of the strain recovery occurs within the first two minutes (Figure 6) of removing the load. The LCE1 film held at a constant strain, the stress is expected to show a decrease [70][71][72][73][74][75] and the equilibrium stress-strain curve would be lower than what is measured in real time. Figure 9 shows representative XRD patterns of LCE1 over a wide q-range (bottom row) and the magnified small angle X-ray scattering (SAXS) patterns (top row).…”
Section: Polydomain-monodomain Transition Under Uniaxial Strainmentioning
confidence: 99%
“…Previous observations on this elastomer indicated that most of the strain recovery occurs within the first two minutes (Figure 6) of removing the load. The LCE1 film held at a constant strain, the stress is expected to show a decrease [70][71][72][73][74][75] and the equilibrium stress-strain curve would be lower than what is measured in real time. Figure 9 shows representative XRD patterns of LCE1 over a wide q-range (bottom row) and the magnified small angle X-ray scattering (SAXS) patterns (top row).…”
Section: Polydomain-monodomain Transition Under Uniaxial Strainmentioning
confidence: 99%
“…Therefore, the FEM model will be used to calculated the global stress distribution in the system. As a result, the PVC can be described as a linear viscoelastic material, which is appropriate for PVC at stresses below the yield stress [10]. To determine 'failure', stresses in the system are compared to a stress threshold that corresponds to failure through crack growth within a given time.…”
Section: Model Asumptions and Failure Criterionmentioning
confidence: 99%
“…These results suggest an increasing heterogeneity of chain dynamics at glass transition; i. e. the chain dynamics is different in different regions of the sample. According to the Addam-Gibbs framework, 28 the characteristic size of these regions must be larger than the size of the cooperative rearrangement region (CRR), which has been determined for various polymers to be in the range 1-4 nm by means of mechanical, 29,30 dielectric, 31,32 and calorimetric 33,34 methods. The spatial heterogeneity in the networks can be understood in terms of increasing free volume due to loosened molecular packing of the networks.…”
Section: Network Characterizationmentioning
confidence: 99%